A cross-sectional comparative study of the monocyte to high-density lipoprotein cholesterol ratio in normal individuals, type 2 diabetes mellitus, and diabetic nephropathy. - Basha, Shaik Yaseen Chand; M.Sarala; Devara, Daya Truphosa; M.Prasad (Student's Journal of Health Research Africa, 2025)
Background Chronic low-grade inflammation plays a pivotal role in the progression of diabetes mellitus and its complications, particularly diabetic nephropathy. The Monocyte to HDL Cholesterol Ratio (MHR) has emerged as a novel inflammatory marker linked with cardiovascular and metabolic disorders. However, its clinical relevance across the spectrum of diabetes and nephropathy remains underexplored. Objective: To compare the MHR among healthy individuals, patients with type 2 diabetes mellitus, and those with diabetic nephropathy, and to evaluate its correlation with renal function markers. Methods A cross-sectional comparative study was conducted among 100 participants divided into three groups: healthy controls (n = 30), diabetes mellitus without complications (n = 35), and diabetic nephropathy (n = 35). Monocyte count, HDL cholesterol levels, and renal function tests (serum creatinine, eGFR) were measured. MHR was calculated as the ratio of absolute monocyte count to HDL cholesterol. Statistical analysis was done using ANOVA and Pearson’s correlation. Results The mean age of participants was 52.9 ± 7.7 years, with no statistically significant age difference among groups. Gender distribution was approximately balanced (55% male, 45% female).MHR values showed a progressive increase from healthy individuals (8.45 ± 1.56) to diabetic patients (13.27 ± 2.31), and were highest in diabetic nephropathy patients (18.65 ± 3.02) (p < 0.001). MHR was positively correlated with serum creatinine (r = 0.52, p < 0.01) and negatively with eGFR (r = -0.47, p < 0.01). Significant intergroup differences were observed across all parameters. Conclusion The study highlights that MHR significantly increases with disease progression from diabetes to diabetic nephropathy and correlates with declining renal function. MHR may serve as a simple, cost-effective inflammatory biomarker for early risk stratification in diabetic patients. Recommendations Routine inclusion of MHR in diabetic monitoring protocols may improve early detection of nephropathy and guide timely interventions in high-risk individuals.